Cultural Nexus Between School and Community - Aryal, Shiva (AMC Journal, 2022)
Culture and education are inseparable as they are simply two sides of the same coin. In this context, this study focuses to explain how does culture work in schooling of Nepal. In so doing, interpretive research design has been used to determine the relationship between schooling and culture, with the experiences of secondary level teacher. Purposive sampling technique has used to select sample population and schooling inventory practice and culture inventory of a society were supervised to the school teacher through the pen-ended interview. This research found positive and significant relationships between schooling and culture. Culture of society can be used by the educators to select the content of school curriculum, learning materials, and methods for communication to student and education as a supportive role to conservation and reformation of culture to a society. The school education mainly dominated by universal culture what Banks called “popular culture”. Further, the exiting schooling limited to the superficial culture of a society rather than the assumption of critical and social action approach of Banks. Therefore, such kinds of schooling can provide general information about the society but does not empower pupils about why do they are behaving different way to the different group of people. This study suggested that the decision making process concerning to school education should be managed in a way, whereas the school teacher, local people, and local expert can easily participate to take initiative or making school curriculum, learning resources and selecting methods of teaching.